The cause and potential solution to the Fusarium wilt disease in banana plants - Sánchez-Espinosa, Ana Claudia; Villarruel-Ordaz, José Luis; Maldonado-Bonilla, Luis (REVISTA TERRA LATINOAMERICANA, 2020)
The Fusarium wilt disease of banana caused by the soil-borne fungal pathogen Fusarium oxysporum f. sp. cubense is currently considered the most prominent disease that threatens the global fruit production. Control of this pathogen is essential to guarantee the supply of banana fruits. The use of chemical pesticides is a common practice for its control; however, this causes contamination of soils, water and atmosphere, and also affects the human health. The knowledge of natural antagonists of Fusarium oxysporum f. sp. cubense is a reliable alternative to develop crop protection strategies. Concerning this, the genus Trichoderma comprises mycoparasitic species adapted to distinct environmental and soil conditions. The features of Trichoderma have enabled its use as an effective biological control agent, but this potential must be extended in order to prevent the economic losses caused by the Fusarium wilt. In this review we present essential information about two contrasting fungal inhabitants of the soil: a group of phytopathogens that produces deleterious consequences in banana plants and its potential antagonists that will provide novel methods of biological control.